2017
DOI: 10.1021/acs.est.6b04218
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Occurrence of N-Chloro-2,2-dichloroacetamide, a Previously Overlooked Nitrogenous Disinfection Byproduct in Chlorinated Drinking Waters

Abstract: Haloacetamides (HAMs) are a class of newly identified nitrogenous disinfection byproducts (N-DBPs) whose occurrence in drinking waters has recently been reported in several DBP surveys. As the most prominent HAM species, it is commonly acknowledged that 2,2-dichloroacetamide (DCAM) is mainly generated from dichloroacetonitrile (DCAN) hydrolysis because the concentrations of these two compounds are often well correlated. Instead of DCAM, a previously unreported N-DBP, N-chloro-2,2-dichloroacetamide (N-Cl-DCAM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Generally, chlorination favours the formation of CF compared to chloramination because Cl2 is 224 more oxidising than NH2Cl [33]. Previous studies have shown that the reaction of NH2Cl with the 225 amide group is insignificant, and it has been proposed that Cl2 first reacts with amide to form an 226 N-haloamide, followed by enolization and subsequent halogenation at the α-carbon group during 227 the chlorination of AM and PAM [23,34]. The data indicate that N-chlorination by Cl2 consumed 228 more active Cl2 than NH2Cl in the initial reaction period because of its stronger oxidising ability 229 (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, chlorination favours the formation of CF compared to chloramination because Cl2 is 224 more oxidising than NH2Cl [33]. Previous studies have shown that the reaction of NH2Cl with the 225 amide group is insignificant, and it has been proposed that Cl2 first reacts with amide to form an 226 N-haloamide, followed by enolization and subsequent halogenation at the α-carbon group during 227 the chlorination of AM and PAM [23,34]. The data indicate that N-chlorination by Cl2 consumed 228 more active Cl2 than NH2Cl in the initial reaction period because of its stronger oxidising ability 229 (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Yu and Reckhow recently showed that that the N-chlorination reaction occurs rapidly during 303 the chlorination or chloramination of molecules that contain amide groups because the hydrogen 304 atoms of the acetamide groups are easily substituted by halogen atoms [23]. The molecular ion 305 cluster of P105 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of 2,2-dichloroacetamide (DCAM)Cl-DCAM), was confirmed as the actual dichloroacetonitrile degradation product in chlorinated drinking waters. It was suspected that N-Cl-DCAM had been erroneously identified as DCAM, becauseits nitrogen-bound chlorine is readily reduced by most commonly used quenching agents(Yu and Reckhow, 2017).Nitrosamines. Computational chemistry methodswere used byBond et al (2017) to calculate molecular descriptors for 64 NDMA precursors containing a dimethylamine (DMA) moiety.…”
mentioning
confidence: 99%